The evaluation of self-compatibility and crossability in the genus Pyrus based on the observation of pollen tubes growth - Wojciech Antkowiak; Andrzej Wojciechowski (Acta Agrobotanica, 2012)
Interspecific compatibility and self-compatibility in Pyrus communis, P. pyraster and P. salicifolia were evaluated. Degree of compatibility was determined by means of fluorescence microscope. Self-incompatibility evaluated on the basis of the pollen tubes growth showed that two cultivars of P. communis (Bera Hardy and Lukasówka) were self-compatible and the other three cultivars were self-incompatible. All ecotypes of P. pyraster are self-incompatible. In interspecific crosses full inter-incompatibility or unilateral self-incompatibility was observed.